Three-dimensional evaluation of the size and dimensional changes of vomer bone in mid-facial deficiency ındividuals - Mohi, Ammar Riyad (My University, 2017)
Vomer Kemiğinin Konumunun ve Boyutlarının Orta-Yüz Yetersizliği Olan Bireylerde Üç Boyutlu Olarak Değerlendirilmesi Amaç: Bu çalışmanın amacı, 1) Orta-yüz yetersizliği olan bireylerde vomer kemiğinin konumsal ve boyutsal morfometrik değişimlerini değerlendirmek, 2) Farklı kranial ve midfasiyal iskeletsel parametrelerde, lineer ve açısal ölçümlerle gruplararası korelasyonun belirlemek ve 3) Vomer kemiğininin 3B rekonstrüksiyon modelini üç farklı yüz profilinde karşılaştırmaktır. Gereç ve Yöntem: Marmara Üniversitesi Diş Hekimliği Fakültesi Ortodontik A. D. arşivinden seçilmiş, normal okluzyonu ve Angle Sınıf III malokluzyonu olan 16-30 yaş arasındaki 96 hastanın CBCT görüntüleri değerlendirildi. Steiner analiziyle hastalar üç gruba ayrıldı: Normal (tip A), Hafif (tip B) ve Şiddetli (tip C) orta-yüz yetersizliği. Kranial, midfasiyal ve vomer bölgesinde, 13 iskeletsel nokta seçilerek doğrusal ve açısal referans düzlemleri çizildi. Vomer kemiğinin 3B rekonstrüktif boyutları, MIMICS 19.0V yazılımıyla ölçüldü ve veriler istatistiksel olarak analiz edildi. Bulgular: Lineer ve açısal ilişkide vomer kemiğinin anterior (p <0.01) ve posterior (P <0.05) düzeysel parametreleri arasında istatistiksel olarak anlamlı ilişki olduğu saptandı ve bu korelasyonun erkeklerde ve şiddetli (tip C) orta-yüz yetersizliği grubunda daha belirgin olduğu görüldü (p<0.01). Vomer kemiğinin 3B rekonstriktif modelinin şiddetli (tip C) grupta daha geniş ve daha uzun şekilde ölçüldüğü ve istatistiksel olarak diğer gruplardan farklı olduğu saptandı (p<0.001). Sonuç: Bu çalışmanın bulguları tüm düzlemlerde orta-yüz bölgesinde, vomer kemiğinin aktif rolünün önemini göstermektedir. Anahtar Sözcükler: MIMICS, Ortodonti, Vomer Kemik, Orta-Yüz Yetersizliği. 1.

Dimensional Evaluation of the Size and Dimensional Changes of Vomer Bone in Mid-Facial Deficiency Individuals. Aim: The aim of this study was 1) To evaluate the vomer bone shape and size changes in relation to midfacial deficiency features. 2) To determine the correlation between different cranial and midfacial skeletal parameters of the vomer bone in both linear and angular measurements. 3) To compare the 3D reconstructed vomer bone models of three groups. Material and Method: CBCT images of 96 patients with normal occlusion and Class III malocclusion were collected from the archive of Orthodontic Department, Faculty of Dentistry, Marmara University. The age of patients was between 16-30 years old. All images were classified into three groups using ANB angle Steiner’s analysis: Normal (type A) group, Mild (type B) and Severe (type C) midfacial hypoplasia groups. Firstly, 13 skeletal points in cranial, midfacial and vomer region level were selected. Then linear and angular reference planes were drawn for shape outline analysis and later the 3D reconstructed models of vomer bone size were measured using Mimics 19.0V software and data were statistically analyzed. Results: There were high significant differences between anterior variables (P< 0.01) followed by posterior variables (P<0.05) of the vomer bone with high positive correlation in linear and angular parameters in all planes of the severe group (type C) and it was higher in males than females. No statistical correlation within different age was found (P>0.01). The size of the 3D reconstructed model of the vomer bone was larger and had elongated pattern in severe group (type C) when compared to other groups (p<0.001). Conclusion: Based on the findings of this study, it was concluded that the vomer bone had an eventual role in preserving the midface contour of class III malocclusion midface complex in all planes. Orthodontics, Vomer Bone, Midfacial Hypoplasia.
Keywords: Ağız hastalıkları; Çene hastalıkları; Diş hastalıkları; MIMICS MIMICS; Radyoloji